Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits. (6th December 2017) - Sharapova, P R; Luo, K H; Herrmann, H; Reichelt, M; Meier, T; Silberhorn, C
Abstract: We present and discuss perspectives of current developments on advanced quantum optical circuits monolithically integrated in the lithium niobate platform. A set of basic components comprising photon pair sources based on parametric down conversion (PDC), passive routing elements and active electro-optically controllable switches and polarisation converters are building blocks of a toolbox which is the basis for a broad range of diverse quantum circuits. We review the state-of-the-art of these components and provide models that properly describe their performance in quantum circuits. As an example for applications of these models we discuss design issues for a circuit providing on-chip two-photon interference. The circuit comprises a PDC section for photon pair generation followed by an actively controllable modified mach–Zehnder structure for observing Hong–Ou–Mandel interference. The performance of such a chip is simulated theoretically by taking even imperfections of the properties of the individual components into account.